Design after capitalism : transforming design today for an equitable tomorrow. - Wizinsky, Matthew (The MIT Press, 2022)
Responding to rising global inequality and convulsions in the financial sector, Matthew Wizinsky offers clearsighted guidelines for a post-capitalist design approach that orients the practice toward intentional systemic change